A prospective study of downhill mountain biking injuries. Issue 7 (17th January 2013) - Becker, Johannes; Runer, Armin; Neunhäuserer, Daniel; Frick, Nora; Resch, Herbert; Moroder, Philipp
Abstract : Background: Downhill mountain biking (DMB) has become an increasingly popular extreme sport in the last few years with high velocities and bold manoeuvres. The goal of this study was to provide information on the pattern and causes of injuries in order to provide starting points for injury prevention measures. Methods: We performed a monthly e-mail-based prospective survey of 249 riders over one summer season ranging from April until September 2011. Results: A total of 494 injuries occurred during the 29 401 h of downhill exposure recorded, of these 65% were mild, 22% moderate and 13% severe, of which 41% led to a total restriction greater than 28 days. The calculated overall injury rate was 16.8 injuries per 1000 h of exposure. For experts it was 17.9 injuries per 1000 h of exposure, which is significantly higher than the 13.4 for professional riders (OR 1.34; 95% CI, 1.02 to 1.75; p=0.03). A significantly higher rate of injury was reported during competition (20 per 1000 h) than during practice (13 per 1000 h) (OR 1.53; 95% CI, 1.16 to 2.01; p=0.0022). The most commonly injured body site was the lower leg (27%) followed by the forearm (25%). Most frequent injury types were abrasions (64%) and contusions (56%). Main causes of injury reported by the riders were riding errors (72%) and bad trail conditions (31%). Conclusions: According to our data DMB can be considered an extreme sport conveying a high risk of serious injury. Strategies of injury prevention should focus on improvements in riders' technique, checking of local trail conditions and protective equipment design.